Does haplodiploidy help drive the evolution of insect eusociality? - Joshi, Chinmay Hemant; Wiens, John J. (Frontiers in Ecology and Evolution, 2023)
Understanding the evolution of eusociality in insects has been a long-standing and unsolved challenge in evolutionary biology. For decades, it has been suggested that haplodiploidy plays an important role in the origin of eusociality. However, some researchers have also suggested that eusociality is unrelated to haplodiploidy. Surprisingly, there have been no large-scale phylogenetic tests of this hypothesis (to our knowledge). Here, we test whether haplodiploidy might help explain the origins of eusociality across 874 hexapod families, using three different phylogenetic comparative methods. Two of the methods used support the idea that the evolution of eusociality is significantly associated with haplodiploidy, providing possibly the first phylogenetic support for this decades-old hypothesis across insects. However, some patterns were clearly discordant with this hypothesis, and one phylogenetic test was non-significant. Support for this hypothesis came largely from the repeated origins of eusociality within the haplodiploid hymenopterans (and within thrips). Experimental manipulations of the data show that the non-significant results are primarily explained by the origins of eusociality without haplodiploidy in some groups (i.e., aphids, termites). Overall, our results offer mixed phylogenetic support for the long-standing hypothesis that haplodiploidy helps drive the evolution of eusociality.